Sand content and Brizalina spathulata relative abundance from La Matilla core (Guadalquivir Basin) - Pérez-Asensio, José N (PANGAEA, 2024)
These data are published in a study (Jiménez-Moreno et al., 2019), which investigates marine sediments from a onland core (La Matilla core, latitude: 37.174103 longitude: -6.724206) from the Guadalquivir Basin (SW Spain). The studied sediments encompass the early Pliocene climatic optimum, a warm and humid period, occurring from 4.4 to 4 Ma. Sand content data were calculated dividing the weight of the sand fraction (> 63 μm) by the total sample weight and multiplying by 100. Sand content (%) was used as a proxy of relative sea-level changes controlling the proximity to coast of the studied site and modifying the amount of coarse-grained detritic input from the continent arriving at the studied site. The relative abundance (%) of the benthic foraminifer Brizalina spathulata was calculated dividing the raw counts of this species into the total number of benthic foraminifera in every sample and multiplying by 100. Variations in B. spathulata along the core was used as proxy for organic matter fluxes to the seafloor likely related to riverine discharge.
Keywords: Benthic foraminifera; Neogene; Sand; Spain